Development of a guaranteed minimum detectable sensor fault diagnosis scheme - Witczak, Marcin; Pazera, Marcin; Majdzik, Paweł; Matysiak, Ryszard (Zielona Góra: Uniwersytet Zielonogórski)
The paper deals with the estimation of sensor faults for dynamic systems as well as the assessment of the uncertainty of the resulting estimates. For that purpose, it is assumed that the external disturbances are bounded within an ellipsoidal domain. This allows considering both stochastic and deterministic process and measurement uncertainties. Under such an assumption, a fault diagnosis scheme is developed with a prescribed convergence rate and accuracy. To achieve fault estimation, a conversion into an equivalent descriptor system is utilized.
Keywords: minimum detectable fault; fault estimation; fault diagnosis; sensor faults